Food Security and State Sovereignty: A Comparative Analysis of Indonesia and Malaysia - Kaslam, Kaslam; Armin; Adi Suryadi B (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2025)
Food security has emerged as a critical policy concern in Southeast Asia, where demographic pressures, climate change, and global market volatility increasingly challenge national food systems. This study provides a comparative analysis of food governance in Indonesia and Malaysia, examining how institutional structures, production strategies, supply chain performance, and import dependency shape each country’s ability to safeguard food security and maintain state sovereignty. Using a qualitative comparative approach supported by policy documents, statistical reports, and scholarly literature, the research identifies fundamental contrasts between the two national models. Indonesia adopts a sovereignty-oriented, multi-agency governance structure that prioritizes rice self-sufficiency and state-led intervention, resulting in strong staple production but limited diversification and logistical inefficiencies. Conversely, Malaysia relies on a centralized, efficiency-driven model characterized by technological integration, rapid policy coordination, and diversified production, yet remains structurally dependent on imported rice. The findings reveal that neither sovereignty-focused nor efficiency-focused approaches alone are sufficient to achieve long-term resilience. Indonesia’s strong domestic production is undermined by reliance on imported inputs, while Malaysia’s advanced logistics cannot fully compensate for dependency on external staple sources. The study argues that hybrid governance models—combining strategic staple sovereignty with diversified, technology-enabled supply chains—offer a more robust pathway for food resilience. Furthermore, regional cooperation through ASEAN presents significant opportunities for complementary integration, leveraging Indonesia’s production strengths and Malaysia’s logistical capacities. Overall, this research contributes to a deeper understanding of the political economy of food systems in Southeast Asia and highlights the need for adaptive, multi-dimensional strategies to strengthen regional food security.